Difference between revisions of "Stewart's Theorem"

(Redirected page to Stewart's theorem)
(Tag: New redirect)
(Tag: Removed redirect)
Line 1: Line 1:
#REDIRECT[[Stewart's theorem]]
+
== Statement ==
 +
 
 +
Given any [[triangle]] <math>\triangle ABC</math> with sides of length <math>a, b, c</math> and opposite [[vertex|vertices]] <math>A</math>, <math>B</math>, <math>C</math>, respectively, then if [[cevian]] <math>AD</math> is drawn so that <math>BD = m</math>, <math>DC = n</math> and <math>AD = d</math>, we have that <math>b^2m + c^2n = amn + d^2a</math>.  (This is also often written <math>man + dad = bmb + cnc</math>, a phrase which invites mnemonic memorization, i.e. "A man and his dad put a bomb in the sink.") That is Stewart's Theorem.
 +
 
 +
[[Image:Stewart's_theorem.png]]
 +
 
 +
== Proof ==
 +
 
 +
=== Proof 1 ===
 +
 
 +
Applying the [[Law of Cosines]] in triangle <math>\triangle ABD</math> at [[angle]] <math>\angle ADB</math> and in triangle <math>\triangle ACD</math> at angle <math>\angle CDA</math>, we get the following equations:
 +
* <math>n^{2} + d^{2} - 2nd\cos{\angle CDA} = b^{2}</math>
 +
* <math>m^{2} + d^{2} - 2md\cos{\angle ADB} = c^{2}</math>
 +
Because angles <math>\angle ADB</math> and <math>\angle CDA</math> are [[supplementary]], <math>m\angle ADB = 180^\circ - m\angle CDA</math>.  We can therefore solve both equations for the cosine term.  Using the [[trigonometric identity]] <math>\cos{\theta} = -\cos{(180^\circ - \theta)}</math> gives us
 +
*<math>\frac{n^2 + d^2 - b^2}{2nd} = \cos{\angle CDA}</math>
 +
*<math>\frac{c^2 - m^2 -d^2}{2md} = \cos{\angle CDA}</math>
 +
Setting the two left-hand sides equal and clearing [[denominator]]s, we arrive at the equation: <math> c^{2}n + b^{2}m=m^{2}n +n^{2}m + d^{2}m + d^{2}n </math>. However, <math>m+n = a</math> so
 +
<cmath>m^2n + n^2m = (m + n)mn = amn</cmath> and
 +
<cmath>d^2m + d^2n = d^2(m + n) = d^2a.</cmath>
 +
This simplifies our equation to yield <math>man + dad = bmb + cnc,</math> as desired.
 +
 
 +
=== Proof 2 (Pythagorean Theorem) ===
 +
 
 +
Let the [[altitude]] from <math>A</math> to <math>BC</math> meet <math>BC</math> at <math>H</math>. Let <math>AH=h</math>, <math>CH=x</math>, and <math>HD=y</math>.
 +
 
 +
We can apply the [[Pythagorean Theorem]] on <math>\triangle AHC</math> and <math>\triangle AHD</math> to yield
 +
 
 +
<cmath>h^2 = b^2 - x^2 = d^2 - y^2<math>  and then solve for b to get  </math>b^2 = d^2 + x^2 - y^2</cmath>
 +
 
 +
Doing the same for <math>\triangle AHB</math> and <math>\triangle AHD</math>
 +
 
 +
<cmath>h^2 = c^2 - (m + y)^2 = d^2 - y^2<math> then solve for c to get </math>c^2 = d^2 + m^2 + 2my</cmath>
 +
 
 +
Now multiple the first expression by m and the second by n
 +
 
 +
<cmath>mb^2 = md^2 + m(x^2 - y^2)</cmath>
 +
<cmath>nc^2 = nd^2 + m^2n + 2mny</cmath>
 +
 
 +
Next add these two expressions
 +
 
 +
<math>mb^2 + nc^2 = md^2 + m(x^2 - y^2) + nd^2 + m^2n + 2mny</math>.
 +
 
 +
Then simplify as follows (we reapply x + y = n a few times while factoring):
 +
 
 +
<cmath>mb^2 + nc^2 = (m + n)d^2 + m(x+y)(x - y) + mn(n + 2y)</cmath>
 +
<cmath>mb^2 + nc^2 = (m + n)d^2 + mn(x - y) + mn(n + 2y)</cmath>
 +
<cmath>mb^2 + nc^2 = (m + n)d^2 + mn(x + y + n)</cmath>
 +
<cmath>mb^2 + nc^2 = (m + n)d^2 + mn(m + n)</cmath>
 +
<cmath>mb^2 + nc^2 = (m + n)(d^2 + mn)</cmath>
 +
 
 +
Rearranging the equation gives Stewart's Theorem:
 +
 
 +
<cmath>man+dad = bmb+cnc</cmath>
 +
 
 +
== Proof 3 (Barycentrics) ==
 +
 
 +
Let the following points have the following coordinates:
 +
 
 +
<math>A: (1,0,0)</math>
 +
 
 +
<math>B: (0,1,0)</math>
 +
 
 +
<math>C: (0,0,1)</math>
 +
 
 +
<math>D: \left(0, \frac{n}{m+n},\frac{m}{m+n}\right)</math>
 +
 
 +
Our displacement vector <math>\overrightarrow{AD}</math> has coordinates <math>\left(1, -\frac{n}{m+n}, -\frac{m}{m+n}\right)</math>. Plugging this into the barycentric distance formula, we obtain <cmath>d^2=-(m+n)^2 \left(\frac{mn}{(m+n)^2} \right)-b^2 \left ( -\frac{m}{m+n} \right)-c^2 \left(-\frac{n}{m+n}\right)=-mn+\frac{b^2m+c^2n}{m+n}</cmath> Multiplying by <math>m+n</math>, we get <math>d^2(m+n)+mn(m+n)=b^2m+c^2n</math>. Substituting <math>m+n</math> with <math>a</math>, we find Stewart's Theorem: <cmath>\boxed{d^2a+amn=b^2m+c^2n}</cmath>
 +
 
 +
== Video Proof ==
 +
 
 +
[//youtu.be/jEVMgWKQIW8 TheBeautyofMath]
 +
 
 +
== See Also ==
 +
 
 +
* [[Menelaus' theorem]]
 +
* [[Ceva's theorem]]
 +
* [[Geometry]]
 +
* [[Angle Bisector Theorem]]
 +
 
 +
[[Category:Geometry]]
 +
[[Category:Theorems]]
 +
{{stub}}

Revision as of 16:33, 18 February 2025

Statement

Given any triangle $\triangle ABC$ with sides of length $a, b, c$ and opposite vertices $A$, $B$, $C$, respectively, then if cevian $AD$ is drawn so that $BD = m$, $DC = n$ and $AD = d$, we have that $b^2m + c^2n = amn + d^2a$. (This is also often written $man + dad = bmb + cnc$, a phrase which invites mnemonic memorization, i.e. "A man and his dad put a bomb in the sink.") That is Stewart's Theorem.

Stewart's theorem.png

Proof

Proof 1

Applying the Law of Cosines in triangle $\triangle ABD$ at angle $\angle ADB$ and in triangle $\triangle ACD$ at angle $\angle CDA$, we get the following equations:

  • $n^{2} + d^{2} - 2nd\cos{\angle CDA} = b^{2}$
  • $m^{2} + d^{2} - 2md\cos{\angle ADB} = c^{2}$

Because angles $\angle ADB$ and $\angle CDA$ are supplementary, $m\angle ADB = 180^\circ - m\angle CDA$. We can therefore solve both equations for the cosine term. Using the trigonometric identity $\cos{\theta} = -\cos{(180^\circ - \theta)}$ gives us

  • $\frac{n^2 + d^2 - b^2}{2nd} = \cos{\angle CDA}$
  • $\frac{c^2 - m^2 -d^2}{2md} = \cos{\angle CDA}$

Setting the two left-hand sides equal and clearing denominators, we arrive at the equation: $c^{2}n + b^{2}m=m^{2}n +n^{2}m + d^{2}m + d^{2}n$. However, $m+n = a$ so \[m^2n + n^2m = (m + n)mn = amn\] and \[d^2m + d^2n = d^2(m + n) = d^2a.\] This simplifies our equation to yield $man + dad = bmb + cnc,$ as desired.

Proof 2 (Pythagorean Theorem)

Let the altitude from $A$ to $BC$ meet $BC$ at $H$. Let $AH=h$, $CH=x$, and $HD=y$.

We can apply the Pythagorean Theorem on $\triangle AHC$ and $\triangle AHD$ to yield

\[h^2 = b^2 - x^2 = d^2 - y^2<math>  and then solve for b to get  </math>b^2 = d^2 + x^2 - y^2\]

Doing the same for $\triangle AHB$ and $\triangle AHD$

\[h^2 = c^2 - (m + y)^2 = d^2 - y^2<math> then solve for c to get </math>c^2 = d^2 + m^2 + 2my\]

Now multiple the first expression by m and the second by n

\[mb^2 = md^2 + m(x^2 - y^2)\] \[nc^2 = nd^2 + m^2n + 2mny\]

Next add these two expressions

$mb^2 + nc^2 = md^2 + m(x^2 - y^2) + nd^2 + m^2n + 2mny$.

Then simplify as follows (we reapply x + y = n a few times while factoring):

\[mb^2 + nc^2 = (m + n)d^2 + m(x+y)(x - y) + mn(n + 2y)\] \[mb^2 + nc^2 = (m + n)d^2 + mn(x - y) + mn(n + 2y)\] \[mb^2 + nc^2 = (m + n)d^2 + mn(x + y + n)\] \[mb^2 + nc^2 = (m + n)d^2 + mn(m + n)\] \[mb^2 + nc^2 = (m + n)(d^2 + mn)\]

Rearranging the equation gives Stewart's Theorem:

\[man+dad = bmb+cnc\]

Proof 3 (Barycentrics)

Let the following points have the following coordinates:

$A: (1,0,0)$

$B: (0,1,0)$

$C: (0,0,1)$

$D: \left(0, \frac{n}{m+n},\frac{m}{m+n}\right)$

Our displacement vector $\overrightarrow{AD}$ has coordinates $\left(1, -\frac{n}{m+n}, -\frac{m}{m+n}\right)$. Plugging this into the barycentric distance formula, we obtain \[d^2=-(m+n)^2 \left(\frac{mn}{(m+n)^2} \right)-b^2 \left ( -\frac{m}{m+n} \right)-c^2 \left(-\frac{n}{m+n}\right)=-mn+\frac{b^2m+c^2n}{m+n}\] Multiplying by $m+n$, we get $d^2(m+n)+mn(m+n)=b^2m+c^2n$. Substituting $m+n$ with $a$, we find Stewart's Theorem: \[\boxed{d^2a+amn=b^2m+c^2n}\]

Video Proof

TheBeautyofMath

See Also

This article is a stub. Help us out by expanding it.